THE MODERN APPROACHES OF FORMATION OF THE REGIONAL TOURIST CLUSTER - Svetlana Zenchenko; Ekaterina Ledeneva (Вестник Северо-Кавказского федерального университета)
The services sector develops higher rates in comparison with production of goods now. One of its most dynamic sectors is tourist. Recognition by the country leaders of prospects of a tourist sector of economy led to acceptance in 2011 of the Federal target program «Development of Internal and Entrance Tourism in the Russian Federation (2011-2018)». In it the tourism role as one «from the important directions influencing growth of economy is justified». Thus, the significance of tourism as «the catalytic agent of social and economic development is emphasized». The clustering of a tourist sector of regional economy is designed to promote completer use of stored potential and its further development, increase in competitiveness of subjects of tourist activities. Therefore regional tourist clusters naturally become a source to increase in productivity, efficiency and competitiveness of the territory.